NONLINEAR SURFACE-WAVE EXCITATIONS IN THE BENARD-MARANGONI SYSTEM - Kraenkel, Roberto André [UNESP]; Pereira, J. G.; Manna, M. A. (American Physical Soc, 1992)
We examine the appearance of surface waves governed by Burgers and Korteweg-de Vries equations in a shallow viscous heated fluid. We consider waves triggered by a surface-tension variation induced by both temperature and concentration gradients. We also establish the range of parameters for which the above-mentioned equations appear.